Proceedings of the 29th ACM International Conference on Multimedia 2021
DOI: 10.1145/3474085.3475413
|View full text |Cite
|
Sign up to set email alerts
|

A2W: Context-Aware Recommendation System for Mobile Augmented Reality Web Browser

Abstract: Augmented Reality (AR) offers new capabilities for blurring the boundaries between physical reality and digital media. However, the capabilities of integrating web contents and AR remain underexplored. This paper presents an AR web browser with an integrated context-aware AR-to-Web content recommendation service named as A2W browser, to provide continuously user-centric web browsing experiences driven by AR headsets. We implement the A2W browser on an AR headset as our demonstration application, demonstrating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The integration of sensors enables AR systems to understand users' current states [99,194,204] and their environment [139,153] to provide a variety of intelligent functionalities. For example, AR could infer user intent [14] and provide contextual recommendations for daily activities (e.g., recipe recommendations when a user opens the fridge during lunch) [15,118,122]. The rich interaction between the outcomes of AI and end-users requires effectively designed XAI that can support users in a variety of contexts, such as when users are confused or surprised while encountering an unexpected AI outcome, or when they want to make sure that an AI outcome is reliable and trustworthy [17,155].…”
Section: 21mentioning
confidence: 99%
See 1 more Smart Citation
“…The integration of sensors enables AR systems to understand users' current states [99,194,204] and their environment [139,153] to provide a variety of intelligent functionalities. For example, AR could infer user intent [14] and provide contextual recommendations for daily activities (e.g., recipe recommendations when a user opens the fridge during lunch) [15,118,122]. The rich interaction between the outcomes of AI and end-users requires effectively designed XAI that can support users in a variety of contexts, such as when users are confused or surprised while encountering an unexpected AI outcome, or when they want to make sure that an AI outcome is reliable and trustworthy [17,155].…”
Section: 21mentioning
confidence: 99%
“…They included 1) music recommendations for the morning when users would be brushing their teeth, 2) podcast recommendations for when users would be driving to work, 3) music recommendations for when users would be working out, 4) recipe recommendations for when users would be making dinner, and 5) additional spice recommendations for when users would be making dinner. In this study, we chose recommendations as the main AI service category, since it is arguably one of the most common AI applications in everyday AR [50,118] and users could easily contextualize these scenes in their mind.…”
Section: Study 1: Large-scale End-user Surveymentioning
confidence: 99%
“…With very limited knowledge of AR-driven empathy, the metaverse will hardly reach the ultimate phase. To this end, it is necessary to link the sole virtual environments with virtual-physical (blended) environments [72,73]. As a prior study revealed that the combination of AR and VR can further engage the users [24], more investigation should be done to achieve the potential of the empathic metaverse.…”
Section: From Virtual Environments To the Metaversementioning
confidence: 99%
“…One prominent strategy is context awareness, e.g., the users, environments, and social dynamics. The edge AIs, e.g., recommendation systems, can parse user context and give the most relevant augmentation [6]. In addition, the current research on user contexts primarily focuses on the users' five senses that are straightforward and factual.…”
Section: Towards Metaverse-user Interactionmentioning
confidence: 99%